HYPODONTIA WITH CLASS I MALLOCLUSION AND MAXILLARY DIASTEMA - Fatimah, Bunga; Ardani, I Gusti Aju Wahju (Indonesian Journal of Dental Medicine, 2018)
Background: Dental agenesis is a term that refers to the absence of one or more teeth, and hypodontia refers to a severe type of tooth agenesis involving less than six or more than one congenitally missing teeth, excluding the third molars. Purpose: This aimed to report the correction of overbite by using intrusion archwires. Case: A 20-year-old female patient had class I malocclusion and deep overbite, incisor retroclination, mild mandibular crowding and agenesis of 12, 13, 14, 15, and 24. Case management: The case was treated with non-extraction using 0.022 pre-adjusted technique to level and unravel using intrusion archwires to correct the deep overbite. Conclusion: The 17-month treatment resulted in a corrected overbite, good occlusion, and good facial aesthetics.